(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study was to investigate and analyze the profile of Professor of Physical Education from the vision of the physical education teachers of secondary education in public schools, municipal, state and private. Using the case study as a methodological procedure, sought through questionnaires raise different opinions that Physical Education teachers had about them, about their teaching practice and their involvement within the school. For analysis and interpretation of results the responses were grouped by public institution, municipal, state and private. Realized with this study that teacher’s profile in the state and county profile different from the teacher’s private school. These differences occur primarily by the financial factor and also the infrastructure that each school has and the way that physical education professionals using the same to conduct their classes.